1998
DOI: 10.1093/bja/80.2.195
|View full text |Cite
|
Sign up to set email alerts
|

Blood salvage during caesarean section

Abstract: The aim of this study was to assess blood salvage during Caesarean section. In 15 Caesarean sections, red cells lost were collected and washed with a Dideco machine and tested for the presence of fetoplacental material, bacterial contamination, free haemoglobin and fetal blood cells. Successive patients were allocated randomly to one of two groups. In group 1 (n = 34), intraoperative blood was salvaged, while group 2 served as a control. The mean amount of blood salvaged in group 1 was 363 (SD 153) ml. Blood w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
82
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(87 citation statements)
references
References 16 publications
(18 reference statements)
4
82
0
1
Order By: Relevance
“…However, the significance of fetal squames and lamellar bodies in the maternal circulation has been questioned as previous studies have confirmed their presence in the circulation of otherwise healthy parturients [6] and patients undergoing caesarean section [5]. Negative bacterial culture of cell-salvaged blood that has not undergone LDF filtration has largely eliminated concerns of bacterial transmission [7]. Transfusion of unfiltered autologous blood therefore remains a theoretical rather than a practical risk.…”
mentioning
confidence: 99%
“…However, the significance of fetal squames and lamellar bodies in the maternal circulation has been questioned as previous studies have confirmed their presence in the circulation of otherwise healthy parturients [6] and patients undergoing caesarean section [5]. Negative bacterial culture of cell-salvaged blood that has not undergone LDF filtration has largely eliminated concerns of bacterial transmission [7]. Transfusion of unfiltered autologous blood therefore remains a theoretical rather than a practical risk.…”
mentioning
confidence: 99%
“…44 However, there were flaws in trial design and conduct, including no explanation of the randomisation method. Furthermore, the control group transfusion rate of 23.5% was at least four times greater than normal practice in the UK.…”
Section: Existing Evidencementioning
confidence: 99%
“…44,68 Factors influencing this figure include country of origin, indication for caesarean section (emergency or elective) and local transfusion policy. Our audits in two centres conducted at the time of study planning put transfusion rates for an unselected caesarean section population at around 5%.…”
Section: Sample Sizementioning
confidence: 99%
See 2 more Smart Citations